Spatially Resolved Insight into the Chemical and Electronic Structure of Solution‐Processed Perovskites—Why to (Not) Worry about Pinholes. Issue 5 (8th January 2018) - Hartmann, Claudia; Sadoughi, Golnaz; Félix, Roberto; Handick, Evelyn; Klemm, Hagen W.; Peschel, Gina; Madej, Ewa; Fuhrich, Alexander B.; Liao, Xiaxia; Raoux, Simone; Abou‐Ras, Daniel; Wargulski, Dan; et al.
Abstract: The unprecedented speed at which the performance of solar cells based on solution‐processed perovskite thin films has increased, in some ways, appears to violate conventional understanding of device optimization. The relatively poor coverage of the TiO2 electron transport layer by the absorber should cause shunting of the cell. This, however, is not the case. In this paper, it is attempted to explain this "discrepancy." Insights into coverage, morphology, local elemental composition, and spatially resolved electronic structure of CH3 NH3 PbI(3− x ) Cl x perovskite absorbers wet‐chemically deposited on planar compact TiO2 electron transport material (ETM) are revealed. Microscopy images indicate an incomplete coverage of the ETM. Depending on the degree of coverage, a variation in iodine oxidation and metallic lead formation is found. With the electronic structure of the absorber and the ETM established experimentally and taking literature on the commonly used hole transport material spiro‐MeOTAD into account, it is revealed that excellent charge selectivity occurs at the interfaces between the absorber and both the hole and electron transport layers. It can also be surmised that, crucially, any direct interface between the TiO2 and spiro‐MeOTAD would be characterized by a large recombination barrier preventing shunts; to some extent minimizing the negative effects of absorber pinholes. Abstract : Spatially resolved chemical and electronic structure investigations of CH3 NH3 PbI(3− x ) Cl x /TiO2 samples show an incomplete coverage and inhomogeneous properties. Varying likelihood of iodine oxidation and metallic lead formation, an excellent charge selectivity at the contact interfaces, and a large recombination barrier between electron and hole transport layer are found, minimizing negative pinhole effects.